The Inclusion of Social Character Values in Buku Bahasa Inggris for 10th Graders (The Journal of Educational Development, 2021)
Textbooks play an important role in teaching and learning activities. The revisions to the curriculum still kept character education at their center, even strengthening its implementation. Indonesia's current president, Mr. Jokowi, has a plan called "mental revolution," which is contained in the 2013 curriculum. This research aims at revealing several social character values that are representing a mental revolution: (1) honesty, (2) discipline, (3) responsibility, (4) care value, (5) politeness value, (6) responsiveness value, and (7) proactive value. The research method is content analysis with a qualitative, descriptive approach. The subject was the English textbook for 10th graders, written by the Ministry of Education and Culture in 2017. The research shows that there were seven social character values in Buku Bahasa Inggris for 10th graders, written by the ministry of education and culture, dominated by the responsibility value (28.1%) and proactive value (26.3%). Discipline and responsiveness, on the other hand, are the least common social character values, appearing with frequency of 2.8% and 0.4%, respectively. The results of this study indicate that the textbook isn’t good enough to be used in teaching and learning activities, and it also doesn’t match Mr. Jokowi’s plan.